To determine which expression evaluates to 1, let's analyze each option:
-
\( 3(8^0) \):
- \( 8^0 = 1 \), so \( 3(8^0) = 3 \times 1 = 3 \).
-
\( (-2.97)^0 \):
- Any non-zero number raised to the power of 0 equals 1, so \( (-2.97)^0 = 1 \).
-
\( 50 + 90 + 5^0 + 9^0 \):
- \( 5^0 = 1 \) and \( 9^0 = 1 \), so this simplifies to \( 50 + 90 + 1 + 1 = 142 \).
-
\( 13 - (7.42)^0 \):
- \( (7.42)^0 = 1 \), so \( 13 - (7.42)^0 = 13 - 1 = 12 \).
Out of these evaluations, the only one that results in 1 is:
Answer: \( (-2.97)^0 \) which equals 1.